2000
DOI: 10.2307/2641029
|View full text |Cite
|
Sign up to set email alerts
|

Arthropods in Urban Habitat Fragments in Southern California: Area, Age, and Edge Effects

Abstract: The distribution of non-ant arthropods was examined in 40 urban habitat fragments in coastal San Diego County, California, USA, to look for effects of fragmentation, proximity to developed edge, and the non-native Argentine ant (Linepithema humile). Arthropods were sampled with pitfall traps and by vacuum sampling from California buckwheat shrubs (Eriogonum fasciculatum). Individual arthropods were identified to order and Recognizable Taxonomic Unit (RTU), or morphospecies. At the fragment scale we looked for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
214
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(226 citation statements)
references
References 46 publications
8
214
0
4
Order By: Relevance
“…In agreement with theory, the small fragment has a low abundance and richness because of its small area and likely also because of strong edge-effects, due to its proportionally higher perimeter (e.g., Murcia 1995; but see Bolger et al 2000). This is consistent with the ANOVA results, where position (inside vs outside fragments) affected the number of individuals and species and its effect varied with the size of the fragment, such that differences in abundance and species richness between inside and outside fragments decreased as fragments become smaller (Figs.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In agreement with theory, the small fragment has a low abundance and richness because of its small area and likely also because of strong edge-effects, due to its proportionally higher perimeter (e.g., Murcia 1995; but see Bolger et al 2000). This is consistent with the ANOVA results, where position (inside vs outside fragments) affected the number of individuals and species and its effect varied with the size of the fragment, such that differences in abundance and species richness between inside and outside fragments decreased as fragments become smaller (Figs.…”
Section: Discussionmentioning
confidence: 59%
“…Area-effects on arthropod abundance and richness have been well established in both experimental and field studies (e.g., Kareiva 1990;Collinge 2000; but see Golden and Crist 2000). Nonetheless, seasonal effects (Bolger et al 2000) have not been fully analyzed with regard to their interaction with area-or edge-effects in fragmented landscapes. In our study, season significantly interacted with the effects of area and position.…”
Section: Discussionmentioning
confidence: 97%
“…The duration of sugar availability may have been insuYcient in relation to known rates of spread (15-270 m/year;Holway et al 2002a). Alternatively, their spread in response to sugar may have been positively mediated by edge eVects linked to the urban boundary Bolger et al 2000;Bolger 2007;Holway 2005) or Argentine ants may depend on edge disturbances limiting them to edge eVect status themselves (Bolger 2007). While this may seem to lessen the capacity for Argentine ants to invade natural habitat even with an available carbohydrate source, ongoing fragmentation of forest from human land-use (Wilcove et al 1986) increases the potential exposure of such habitat to Argentine ants Bolger 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Not all introduced species cause declines in their native counterparts. For example, Bolger et al (2000) found that native spiders and carabid beetles increased in abundance with increasing fragment age, despite increases in exotic species in these habitat fragments. Our results were similar in that native centipedes did not appear to decline with decreasing fragment size.…”
Section: Discussionmentioning
confidence: 96%